Peran dan Dampak Teknologi Digital Pada Disain Interior FSR ISI Yogyakarta - Martino Dwi Nugroho (Ars: Jurnal Seni Rupa dan Desain, 2011)
The Role and Impact of  Technology on the Interior Design Study Program of  ISI Yogyakarta. Digital technology grows rapidly and covers all fields in life. The design education conducted by the Visual Art Faculty of  ISI Yogyakarta manages to cope with the technology development. This progress does not only set changes in technical aspects such as equipment and material, but also includes a wider range of  issues correlated with the designing concept, the users’ responses and the designers’ attitude in the process of  creating their works of  art. The development of  interior design in Indonesia can be tracked from four periods of  development: the colonization era, the guided democracy era, the new order era, and the 21st century design era. The Interior Design Study Program, as other study programs existing in the Faculty of  Visual Art of  ISI Yogyakarta is branded for excellent manual skills. The application of  digital technology in its teaching-learning process should ponder many aspects: hardware, software, maintenance, and human capital. Thoughtful researches are required to be able to follow the world development and show the uniqueness of  this art education institution.Keywords: digital, the history of  interior design.